The Effect of Concentration Areca Seed Extract (Areca Catechu L.) on Physicochemical and Sensory Properties of Pineapple Juice (Ananas Comosus L. Merr) As a Functional Beverages - Purba, Daniel Tua; Nizori, Addion; Wulansari, Dian (Indonesian Food Science and Technology Journal, 2022)
This study aims to determine the effect of concentration areca seed extract on the physicochemical and sensory properties of pineapple juice as a functional beverages , and to determine the appropriate concentration of areca seed extract to produce pineapple juice that has the best physicochemical and sensory properties. This study used a completely randomized design (CRD) consisting of 4 levels of treatment, namely the concentration of areca seed extract 0%, 1%, 2%, and 3% (v/v). Each treatment was repeated 5 times, so there were 20 experimental units. The results showed that the concentration of areca seed extract had a significant effect on the total soluble solids, the degree of warmth L* and a*, antioxidant activity, total tannin, vitamin C levels, and had no significant effect on the acidity (pH), and had a characteristic taste of pineapple chelate until the taste of pineapple is slightly chelate, the color is brown to very brown, it has a pineapple aroma to a strong pineapple aroma, with a weak aftertaste to a slightly strong after taste. The best treatment in making pineapple juice with areca seed extract was the concentration of 2% areca seed extract which contained 80.02% antioxidant activity, vitamin C 104.68 mg/100 g, total tannin 99.62 mg TAE/g, total dissolved solids value 20.980brix, color degree value L*29.48, a*7.06, b*20.80, acidity value (pH) 3.37, has a slightly brown color, aroma of pineapple (methyl ester and ethyl ester compounds), taste pineapple and not chelate, and has no aftertaste.